PWE-037 Proton pump inhibitors and hypomagnesaemia. (28th May 2012) - Hebbar, S; Sharma, N; Wilson, P
Abstract : Introduction: Hypomagnesaemia is a rare and potentially serious complication of PPI therapy. About 30 cases of severe hypomagnesaemia have been reported in long term PPI users. 1 Methods: We describe two cases recently admitted to our hospital with symptomatic hypomagnesaemia and a history of long term PPI usage. Results: Patient 1—A 54-year-old female was admitted with nausea, vomiting and abdominal discomfort for few months. Patient was on lansoprazole for more than a year. On admission, magnesium level was 0.42 mmol/l. Patient was treated with magnesium supplements and was sent home with increased dose of lansoprazole. Over the next few weeks, magnesium level dropped to 0.4 mmol/l in spite of supplementation. On stopping PPI, magnesium returned to normal levels in 4 weeks time. Patient 2—A 75-year-old female was admitted with vomiting and lethargy. Patient was on PPI for more than 18 years. Magnesium level was 0.13 mmol/l and calcium 1.62 mmol/l. Patient was treated with intravenous supplements and discharged on oral magnesium. Within 2 months, patient was readmitted with similar complaints and magnesium level was again noted to be 0.13 mmol/l. OGD and CT abdomen were normal. Urinary magnesium levels were normal. Magnesium levels did not normalise in spite of supplementation. Omeprazole was stopped and magnesium started improving over the next 4 weeks. Conclusion: Hypomagnesaemia is a under recognised complication of long term PPI therapy, which responds rapidly on stopping PPI. In few of the reported cases, a causal relationship with PPI use has been established by recurrence of hypomagnesaemia after rechallenge. 2 The cause of hypomagnesaemia is poorly understood. Mutation of TRPM 6/7 gene which is involved in the active transcellular pathway of intestinal absorption of magnesium is one of the postulated mechanism. 2 Monitoring magnesium levels in patients on long term PPI should be considered. 3 This rare complication might not even be so uncommon as more people become aware of the association. Competing interests: None declared. References: 1. Cundy T, Mackay J. Proton pump inhibitors and severe hypomagnesaemia. Curr Opin Gastroenterol 2011;27 :180–5. 2. Negri AL, Valle EE. Hypomagnesaemia/hypokalemia associated with the use of esomeprazole. Curr Drug saf 2011;6 :204–6. 3. FDA Drug Safety Communication . Low Magnesium Levels can be Associated with Long-Term use of Proton Pump Inhibitor drugs (PPIs) .